A modified sequential vascular control strategy in robot‐assisted level III–IV inferior vena cava thrombectomy: initial series mimicking the open 'milking' technique principle. (16th May 2020) - Shen, Donglai; Du, Songliang; Huang, Qingbo; Gao, Yu; Fan, Yang; Gu, Liangyou; Liu, Kan; Peng, Cheng; Xuan, Yundong; Li, Pin; Li, Hongzhao; Ma, Xin; et al.
Abstract : Objective: To introduce a modified sequential vascular control strategy, mimicking the open 'milking' technique principle, for the early release of the first porta hepatis (FPH) and to stop cardiopulmonary bypass (CPB) in level III–IV robot‐assisted inferior vena cava (IVC) thrombectomy (RA‐IVCTE). Patients and methods: From November 2014 to June 2019, 27 patients with a level III–IV IVC tumour thrombus (IVCTT) underwent RA‐IVCTE in our department. The modified sequential control strategy was used in 12 cases. Previously, we released the FPH after the thrombus was resected and the IVC was closed completely, and CPB was stopped at the end of surgery (15 patients). Presently, using our modified strategy, we place another tourniquet inferior to the second porta hepatis (SPH) once the proximal thrombus is removed from the IVC below the SPH. Then, we suture the right atrium and perform early release of the FPH, and stop CPB. Finally, tumour thrombectomy, vascular reconstruction, and radical nephrectomy are performed. Results: Compared with the previous strategy, the modified steps resulted in a shorter median FPH clamping (19 vs 47 min, P < 0.001) and CPB times (60 vs 87 min, P < 0.05); a lower rate of Grade II–IV perioperative complications (25% vs 60%, P < 0.05); and better postoperative hepatorenal and coagulation function, including better median serum alanine aminotransferase (172.7 vs 465.4 U/L, P < 0.001), aspartate aminotransferase (282.4 vs 759.8 U/L, P < 0.001), creatinine (113.4 vs 295 μmol/L, P < 0.01), blood urea nitrogen (7.3 vs 16.7 mmol/L, P < 0.01), and D‐dimer (5.9 vs 20 mg/L, P < 0.001) levels. Conclusion: With the early release of the FPH and stopping CPB, the modified sequential vascular control strategy in level III–IV RA‐IVCTE reduced the perioperative risk for selected patients and improved the feasibility and safety of the surgery. We would recommend this approach to other centres that plan to develop robotic surgery for renal cell carcinoma with level III–IV IVCTT in the future.